Conflicted memories : Europeanizing contemporary histories - Jarausch, Konrad 1941- Hrsg; Lindenberger, Thomas 1955-; Ramsbrock, Annelie MitwirkendeR (Studies in contemporary European history, 2007)
History of memory, policies of the past: what for? / Henry Rousso -- Communist legacies in the 'new Europe': history, ethnicity, and the creation of a 'socialist' nation in Romania, 1945-1989 / Drago¿ƒ Petrescu -- Writing national histories in Europe: reflections on the pasts, presents, and futures of a tradition / Stefan Berger -- Between Europe and the nation: the inward turn of contemporary historical writing / Pieter Lagrou -- War and conflict in contemporary European history, 1914-2004 / John Horne -- In search of a second historicization: national socialism in a transnational perspective / Kiran Klaus Patel -- The origins of the Cold War in Eurasia: a borderland perspective / Alfred J. Rieber -- Europe as leisure time communication: tourism and transnational interaction since 1945 / Thomas Mergel -- Integration from below? migration and European contemporary history / Karen Sch(c)œnw(c)Þlder -- Twentieth-century culture, 'Americanization,' and European audiovisual space / Marsha Siefert -- Economics of western European integration? proving the benefits / Andr(c)♭ Steiner -- A European civil society? / Hartmut Kaelble -- International socialist attempts ad bridge-building in the early postwar period / (c)rjan Appelqvist -- Nation building in the era of integration: the case of Moldova / Igor Ca¿ƒu -- The subject(s) of Europe / Michael Geyer Geyer